Considerations on the Obstacles That Lead to Slow Recruitment in a Pain Management Clinical Trial: Experiences from the Belgian PELICAN (PrEgabalin Lidocaine Capsaicin Neuropathic Pain) Pragmatic Study - Guy H. Hans; Dima Almeshal; Lotte Vanlommel; Ella Roelant; Iris Verhaegen; Elke Smits; Koen Van Boxem; Robert Fontaine; The PELICAN Investigators Team (Pain Research and Management)
Background. A qualitative evaluation study of the prematurely terminated PrEgabalin Lidocaine Capsaicin Neuropathic Pain (PELICAN) study was performed. The PELICAN study aimed to examine pain management for localized neuropathic pain (LNP), as epidemiological figures have shown a high percentage of LNP patients in Belgium. The study compared systemic and topical medications according to pain relief, adverse effects, and several measures of quality of life. Objective. Achieving better study patient recruitment through qualitative research. To investigate and determine the causes of the observed recruitment problems in the PELICAN study, pain centers involved in the study as well as nonrecruiting pain centers were included. Furthermore, it aimed to highlight the positive and negative lessons learned from the conducted study and the number of obstacles the team had to overcome. Methods. A qualitative study, using a mixed methods approach, was performed. Multiple pain centers in Belgium completed an online survey, after which a structured interview was conducted to elaborate the responses in more detail. The broad topics of these meetings were feedback about the study, reviewing survey answers, and actions undertaken to enhance recruitment. Results. Different factors contributed to the low recruitment rate in the PELICAN study, such as limited and late referral from the general practitioners to the Belgian pain centers, insufficient internal referrals from nonpain specialists, lack of specific expertise on LNP in some centers, scarcity of staff, limited reimbursement to administer complex analgesic schemes, overestimation of the patient population, and the reluctance of patients to participate in pain research. Additionally, shortcomings in the implemented study design and the need for more logistical investments were identified. Conclusion. The findings of the qualitative study demonstrate the need for further, more varied LNP research in Belgium, not limited to pharmacological studies. It also sheds important light on the recruitment obstacles that may be faced during these studies. Future studies could support this research by offering better proposals for feasibility and recruitment, for instance, by designing and conducting a compelling pilot study or applying social media during the recruitment phase. Clinical Trials. This trial is registered with NCT03348735. EUDRACT number 2018-003617-17.